Construction of imidazole-based ionic liquid modified MoO3-x for enhancing photocatalytic oxidation desulfurization in diesel - Suhang Xun; Chenchao Hu; Bohan Yang; Wei Jiang; Minqiang He; Wenshuai Zhu; Huaming Li (Green Energy & Environment)
Development of clean desulfurization process that combines both efficient and environmentally friendly remains a significant challenge for diesel production. The photocatalytic oxidation desulfurization technology is regarded as a promising process depending on the superior electron transfer and visible light utilization of photocatalyst. Herein, the nonstoichiometry MoO3-x with outstanding photoresponse ability is prepared and modified by imidazole-based ionic liquid [C12mim]Cl to upgrade electronic structure. The interface H-bonding between MoO3-x and [C12mim]Cl regard as electronic transfer channel and the recombination of e−-h+ pairs is effectively inhibited with the modification of [C12mim]Cl. Deep desulfurization rate of 96.6% can be reached within 60 min and the MoO3-x/[C12mim]Cl (MoC12) photocatalyst demonstrated outstanding cyclic stability within 7 cycles in an extraction coupled photocatalytic oxidation desulfurization (ECPODS) system. The study provides a new perspective on enhancing photocatalytic desulfurization through defect engineering and surface modification.